2022
DOI: 10.1093/plphys/kiac334
|View full text |Cite
|
Sign up to set email alerts
|

A secreted fungal subtilase interferes with rice immunity via degradation of SUPPRESSOR OF G2 ALLELE OF skp1

Abstract: Serine protease subtilase, found widely in both eukaryotes and prokaryotes, participates in various biological processes. However, how fungal subtilase regulates plant immunity is a major concern. Here, we identified a secreted fungal subtilase, UvPr1a, from the rice false smut (RFS) fungus Ustilaginoidea virens. We characterized UvPr1a as a virulence effector localized to the plant cytoplasm that inhibits plant cell death induced by Bax. Heterologous expression of UvPr1a in rice (Oryza sativa) enhanced plant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…Among these, UvPr1a and UvPR1H affect mycelial growth and the conidiation and pathogenicity of U. virens. UvPr1a directly targets and degrades the rice protein OsSGT1 (SUPPRESSOR OF G2 ALLELE OF skp1 ), thereby interfering with host immunity and promoting infection ( 39 ). UvPr1H is a β-hydroxybutyrylated virulence effector, but whether the K bhb of UvPr1H affects its degradation activity to regulate the virulence of U. virens remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Among these, UvPr1a and UvPR1H affect mycelial growth and the conidiation and pathogenicity of U. virens. UvPr1a directly targets and degrades the rice protein OsSGT1 (SUPPRESSOR OF G2 ALLELE OF skp1 ), thereby interfering with host immunity and promoting infection ( 39 ). UvPr1H is a β-hydroxybutyrylated virulence effector, but whether the K bhb of UvPr1H affects its degradation activity to regulate the virulence of U. virens remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…U. virens secretes a large number of effectors to facilitate host colonization. Multiple effector proteins, including SCRE1, SCRE2/UV_1261, SCRE4, SCRE6, UvSec117, UvPr1a, and UvCBP1, inhibit plant immunity and enhance the pathogenesis of U. virens (Chen, Duan, et al, 2022 ; Chen, Li, et al, 2022 ; Fang et al, 2019 ; Li et al, 2021 ; Li et al, 2022 ; Qiu et al, 2022 ; Yang et al, 2022 ; Zhang, Yang, et al, 2020 ; Zheng et al, 2022 ). It is worthwhile to confirm these hypotheses in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, UvPr1a has been identified as a virulence effector in U. virens . The mycelial growth rate of the ∆ UvPr1a mutants is slightly reduced compared with that of the wild type and complemented strains (Chen, Li, et al, 2022 ). Accordingly, it will be interesting to study how UvGHF1 positively affects mycelial growth and contributes to virulence in U. virens .…”
Section: Discussionmentioning
confidence: 99%
“…virens based on genomic analysis (Zhang et al ., 2014, 2021). Recent studies have demonstrated that a number of these effectors play critical roles in infection, including SCRE1, SCRE4, SCRE6, SGP1, UvCBP1, UvPr1a, and UvSec117 (Chen et al ., 2022a,b; Li et al ., 2021a; Qiu et al ., 2022; Song et al ., 2021; Yang et al ., 2022; Zhang et al., 2020; Zheng et al ., 2022). For example, the effector SCRE6 acts as a tyrosine phosphatase that dephosphorylates the negative defence regulator OsMPK6 (MAP Kinase) to enhance its accumulation, thereby inhibiting rice immunity (Zheng et al ., 2022).…”
Section: Introductionmentioning
confidence: 99%